Comparative analysis of sloshing effects on elevated water tanks’ dynamic response using ANN and MARS - Tahera; Neethu Urs; K. Shashi Raj; Rakesh Kumar; Harish Soundalgekar; T. Deepa; Mohd Asif Shah (Discover Materials)
Abstract Important infrastructure elements like elevated water tanks are vulnerable to fluid sloshing brought on by earthquakes, which can seriously harm the structure. In order to precisely capture the fluid–structure interaction, this work uses a 3D finite element model based on the Coupled Eulerian–Lagrangian (CEL) approach to investigate the dynamic response of raised water tanks under seismic excitation. Seismic ground motions were applied to the model, and the displacements, accelerations, and stresses that resulted were examined. The results highlight how fluid sloshing significantly affects the dynamic response of the tank because sloshing waves increase structural stresses and deformations by imposing large hydrodynamic pressures on the tank walls. The water tank's performance as a tuned liquid damper (TLD) was also evaluated in the study. Multivariate Adaptive Regression Splines (MARS) and Artificial Neural Network (ANN) models were created and trained in order to further examine and forecast the dynamic response. According to statistical analysis and Taylor diagram evaluation, the ANN model outperformed the MARS model in forecasting the displacement response. The numerical simulations and precise results were made possible by the use of ABAQUS software, a potent finite element analysis tool. The study's conclusions can be used to improve the analysis and construction of elevated water tanks in order to reduce seismic risk. The impact of different tank geometries, fluid characteristics, and seismic ground motions on the dynamic response of raised water tanks may be investigated in future studies. This research innovatively employs ABAQUS software to simulate the stabilizing effect of sloshing in steel structures during earthquakes. By optimizing water levels to 60% capacity, the study explores sloshing as a potential damping mechanism to mitigate structural vibrations. In comparison to empty tanks, this leads to better damping throughout velocity, acceleration, and displacement responses, which speeds up stabilization and lowers dynamic loads. The study also demonstrates how well adjusted liquid dampers (TLDs) reduce vibrations in raised water tanks.